The bookseller and binder Manuel Millana in the Royal Academy of Fine Arts of San Fernando - Flores Hernández, Yohana Yessica; Carpallo Bautista, Antonio; Moro Pajuelo, Marisa (Revista General de Información y Documentación, 2019)
The main objective of this article is to study the work done by the bookseller and binder Manuel Millana in the Royal Academy of Fine Arts of San Fernando, between 1776 and 1810, at the Royal Academy of Fine Arts of San Fernando, carried out by consulting the books of accounts and files of the Archive of the Academy and the on-site analysis of the bindings described in the documentation, thus knowing better the type of bindings ordered, their prices, materials, recipients, helping to better understand the history of the institution itself, the guild of booksellers, printers and bookbinders from Madrid and therefore of the Madrid society of the time.